The Correlation of Attitudes and Availability of Facilities with the Behaviors of the Community in Disposing of Household Waste in the Sago River - Ningsih, K W (KnE Life Sciences, 2019)
Based on a report from Directorate General of Pollution and Environmental Damage Control of the Ministry of Environment and Forestry (KLHK), in 2015 nearly 68 percent or the majority of the water quality in 33 provinces of Indonesia were heavily polluted. The main source of river pollutants is domestic or household waste. Sanitary Office of Pekanbaru City records the waste produced by around 1.3 million residents of Pekanbaru city is 500 tons / day or 2.6 kilograms per recident everyday. The purpose of this research was to determine the factors corresponding with the behavior of the society in disposing of household waste in the Sago river. This research included into quantitative type with a crosssectional approach. The independent variables of this research were attitudes and availability of facilities. The population were all housewives who live around the Sago River of Sukaramai Village in Pekanbaru city, which is about 974 families. The samples were 284 people which taking them by Stratified Random Sampling Technique. The instruments used were questionnaire and observation sheet. Primary data was obtained through questionnaire and observation while secondary data was from Sukaramai village data in Pekanbaru Kota Subdistrict. Data analysis used chi square test with